Clinical efficacy of unilateral laminotomy for bilateral decompression in the treatment of adjacent segment disease after lumbar fusion - Xu, Yun; Liu, Yang; Ding, Ding; Ru, Bin; Wan, Quan; Ji, Zhongwei; Liu, Wenlong; Guo, Ran; Hu, Jiaqi; Zhang, Nannan; Xu, Langhai; Li, Shun; et al. (Frontiers in Surgery, 2024)
ObjectiveTo assess the clinical impact of unilateral laminotomy for bilateral decompression (ULBD) in managing patients with adjacent vertebrae following lumbar fusion.MethodsA retrospective analysis was conducted on 21 patients, with a mean age of 67.4 years, who underwent ULBD for adjacent vertebra disease at our department from January 2021 to November 2023. We reviewed demographic data, surgical techniques, imaging studies, and patient-reported outcomes. The study compared Visual Analog Scale (VAS) scores, Numeric Rating Scale (NRS) scores, Japanese Orthopaedic Association (JOA) scores, Short Form-36 (SF-36) scores, and imaging outcomes before surgery, immediately post-surgery, and at 1 month, 6 months, and 12 months post-surgery.ResultsEvaluation of 21 patients with adjacent segment disease (ASD) (13 males, 8 females; mean age 67.42 years) was performed with follow-ups at various intervals post-surgery. Postoperative VAS, NRS, JOA, and SF-36 scores showed significant improvements compared to preoperative scores. Immediately after surgery, there were significant improvements in NRS score (2.76 ± 0.70 vs. 3.71 ± 0.85, P < 0.05) and JOA score (15.38 ± 1.02 vs. 9.29 ± 1.01, P < 0.05) compared to preoperative scores. Similarly, at 12 months post-surgery, significant improvements were observed in NRS score (1.52 ± 0.51 vs. 3.71 ± 0.85, P < 0.05) and JOA score (25.0 ± 1.10 vs. 9.29 ± 1.01, P < 0.05) compared to preoperative scores. The clinical satisfaction rate was 95.0% among all patients, with postoperative imaging examinations revealing a significant decompression effect. No complications were reported among the surgical patients.ConclusionsThis study suggests that endoscopic ULBD can be a safe and effective technique for managing symptomatic ASD, providing satisfactory clinical outcomes for patients with ASD. Endoscopic ULBD may serve as an alternative treatment option for ASD with lumbar stenosis.